1986
DOI: 10.7326/0003-4819-104-4-467
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Pretreatment Immunization and Post-treatment Boosting with Bacterial Polysaccharide Vaccines in Patients with Hodgkin's Disease

Abstract: Overwhelming sepsis is a serious complication of staging splenectomy in Hodgkin's disease. To define an optimal immunization strategy, 51 patients received 14-valent pneumococcal, Haemophilus influenzae type b, and meningococcal group C vaccines before therapy and 2 to 12 months after completion of therapy. Natural antibody levels to bacterial polysaccharide antigens and the response to immunization were normal or only minimally impaired in patients with Hodgkin's disease compared with findings in healthy adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…Further, pneumococcal sepsis may occur with strains not represented in the vaccine: this may account for up to 15% of cases of pneumococcal sepsis. 19 The other major question that requires answering is how often immunisations should be given. The original work in immunocompetent patients has suggested that antibodies to pneumococcal polysaccharides remain increased for at least 10 years, 20 although it appears that splenectomised patients may lose their antibody faster and require reimmunisation after three to five years.…”
Section: Discussionmentioning
confidence: 99%
“…Further, pneumococcal sepsis may occur with strains not represented in the vaccine: this may account for up to 15% of cases of pneumococcal sepsis. 19 The other major question that requires answering is how often immunisations should be given. The original work in immunocompetent patients has suggested that antibodies to pneumococcal polysaccharides remain increased for at least 10 years, 20 although it appears that splenectomised patients may lose their antibody faster and require reimmunisation after three to five years.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that a second dose of influenza vaccine can enhance the antibody response in both children and adults receiving chemotherapy who mounted an inadequate immunologic response to the initial dose. [38][39][40][41] Whether the administration of additional or "booster" doses, or increasing the concentration of the antigen contained within the vaccine 42,43 will improve the effectiveness of the vaccine remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the risk of apSI, vaccination against pneumococci is advised in the r\etherlands (1cl). By preference the vaccination is given befare splenectomy because of a higher level of antibodies that is reached (17). For patients suffering from Hodgkin's disease the efficiency is thought to be higher if the vaccination is given before the start of chemotherapy (16).…”
Section: Responsementioning
confidence: 99%